2016
DOI: 10.1038/ncomms11870
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, structure and convergent evolution of the global sponge microbiome

Abstract: Sponges (phylum Porifera) are early-diverging metazoa renowned for establishing complex microbial symbioses. Here we present a global Porifera microbiome survey, set out to establish the ecological and evolutionary drivers of these host–microbe interactions. We show that sponges are a reservoir of exceptional microbial diversity and major contributors to the total microbial diversity of the world's oceans. Little commonality in species composition or structure is evident across the phylum, although symbiont co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
773
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 548 publications
(905 citation statements)
references
References 63 publications
57
773
5
4
Order By: Relevance
“…We recovered a total of 169 OTUs for the combined sponge samples, and just 72 OTUs in adults alone, which is toward the lower end of the range (50-3820) currently known from adult marine sponge microbiomes (Thomas et al, 2016). We do note, however, that our study had relatively low sequencing depth, which could have compromised the recovery of rarer OTUs.…”
Section: Amphimedon Queenslandica Adults House a Low Complexity Micromentioning
confidence: 82%
See 3 more Smart Citations
“…We recovered a total of 169 OTUs for the combined sponge samples, and just 72 OTUs in adults alone, which is toward the lower end of the range (50-3820) currently known from adult marine sponge microbiomes (Thomas et al, 2016). We do note, however, that our study had relatively low sequencing depth, which could have compromised the recovery of rarer OTUs.…”
Section: Amphimedon Queenslandica Adults House a Low Complexity Micromentioning
confidence: 82%
“…These observations raise question about the relative importance of animal hosts and the core symbionts themselves in regulating the assembly and maintenance of the total microbiome through the host life cycle, and in homeostasis of host functionality (Thomas et al, 2016). In an ontogenetic context, numerous studies have demonstrated vertical inheritance of putatively core symbionts during development of embryos and larvae, based on evidence from electron microscopy (see for example Ereskovsky et al, 2005;Oren et al, 2005;Maldonado, 2007;Schmitt et al, 2008) or sequencing of prokaryotic 16S rRNA gene amplicons (see for example Oren et al, 2005;Enticknap et al, 2006;Schmitt et al, 2007Schmitt et al, , 2008Sharp et al, 2007;Steger et al, 2008;Lee et al, 2009;Webster et al, 2010;Gloeckner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistent presence of dominant bacterial phylotypes in several species of sponge indicates that many specific hostmicrobe associations are stable over time, likely facilitated by vertical inheritance (Taylor et al, 2007b;Erwin et al, 2012;Hentschel et al, 2012;Thomas et al, 2016). In non-sponge host-symbiont systems, the temporal stability of associations involving two or more unrelated bacterial symbionts (Takiya et al, 2006;Wu et al, 2006;Dubilier et al, 2008;Zimmermann et al, 2014) has been postulated to involve the use of different energy sources to reduce competition between the bacterial species (Duperron et al, 2006;Kleiner et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%